An updated ground thermal properties database for GSHP applications. (May 2020) - Dalla Santa, Giorgia; Galgaro, Antonio; Sassi, Raffaele; Cultrera, Matteo; Scotton, Paolo; Mueller, Johannes; Bertermann, David; Mendrinos, Dimitrios; Pasquali, Riccardo; Perego, Rodolfo; Pera, Sebastian; Di Sipio, Eloisa; et al.
Highlights: The design of a new GSHP system cannot disregard local ground thermal properties. The ground thermal properties also affect the system long-term energetic performances. A thermal properties database is proposed for both rocks and unconsolidated sediments. It integrates and compares literature data with more than 400 direct measurements. Abstract: When a new ground source heat exchanger field is planned, underground thermal properties input data are necessary for the correct sizing of the geo-exchange system. To support the design, the EU founded Cheap-GSHPs project developed a Decision Support System, that comprises a new database of thermal properties for both rocks and unconsolidated sediments. The thermal properties database has been developed by integrating and comparing data (1) provided by the most important international guidelines, (2) acquired from a wide literature review and (3) obtained from more than 400 direct measurements. The data are mainly thermal conductivity data, hence the convective contribution provided by groundwater flow to heat transfer is not included. This paper presents and analyses the collected database.